Effects of discontinuous Percoll gradient centrifugation on the quality of bovine spermatozoa evaluated with computer-assisted semen analysis and fluorescent probes association - Oliveira, L. Z. [UNESP]; Arruda, R. P.; Celeghini, E. C. C.; de Andrade, A. F. C.; Perini, A. P. [UNESP]; Resende, M. V. [UNESP]; Miguel, M. C. V. [UNESP]; Lucio, A. C. [UNESP]; Hossepian de Lima, V. F. M. [UNESP] (Wiley-Blackwell, 2012)
The objective of this study was to evaluate the quality of bovine frozen-thawed sperm cells after Percoll gradient centrifugation. Frozen semen doses were obtained from six bulls of different breeds, including three taurine and three Zebu animals. Four ejaculates per bull were evaluated before and after discontinuous Percoll gradient centrifugation. Sperm motility was assessed by computer-assisted semen analysis and the integrity of the plasma and acrosomal membranes, as well as mitochondrial function, were evaluated using a combination of fluorescent probes propidium iodide, fluorescein isothiocyanate-conjugated Pisum sativum agglutinin and 5,5',6,6'-tetrachloro-1,1',3,3'-tetraethylbenzimidazolcarbocyanine iodide. The procedure of Percoll gradient centrifugation increased the percentage of total and progressive sperm motility, beat frequency, rectilinear motility, linearity and rapidly moving cells. In addition, the percentage of cells with intact plasma membrane and mitochondrial membrane potential was increased in post-centrifugation samples. However, the percentage of sperm cells with intact acrosomal membrane was markedly reduced. The method used selected the motile cells with intact plasma membrane and higher mitochondrial functionality in frozen-thawed bull semen, but processing, centrifugation and/or the Percoll medium caused damage to the acrosomal membrane.
Keywords: Acrosome integrity; Cryopreserved semen; sperm selection